Pengaruh Kecerdasan Emosional Terhadap Motivasi Belajar Siswa Kelas VIII SMPN 6 Bukittinggi - Faisal Kurnia; Mutiara Rahma Eldita; Zahwa Saviola Ramadhini; Fadila Lailatul Isttianah; Elvita Putri; Aliyan Syarif Mukhtar (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Student motivation to learn is an issue that must be paid attention to by everyone, be it the family or the school. Entering adolescence, children will more often experience ups and downs in motivation when studying, ups and downs in learning motivation are influenced by poor emotional intelligence. The aim of this research is to find out the effect of emotional intelligence on the learning motivation of class VIII students at SMPN 6 Bukittinggi. The technique used for sampling was a purposive sampling technique with an instrument in the form of a questionnaire which was distributed to 123 students. The results of the analysis show that emotional intelligence has a significant influence on learning motivation with a correlation value of 0.353 and a coefficient of determination of 0.125. In conclusion, emotional intelligence has an influence of 12.5% ​​on learning motivation, while 87.5% is influenced by other factors not examined in this research. It is hoped that the results of these findings can encourage schools and families to help students have good emotional intelligence so that students have good motivation to learn.Emotional Intelligence